Enhancing evaporation of liquid by surface heating - Teo, Eric Joo Leng. (2012)
Evaporation is an importance to preserving the Earth’s temperature and many engineering applications as well. This report presents an experimental investigation of water evaporation at a flat surface by surface heating. An evaporator was designed to have heater element aligned parallel to one another at the top of the evaporator and another pair of heaters positioned 5mm below the top heater. This is done so that the evaporation rate of top and bottom heater can be compared. Three thermocouples were positioned to take the temperatures of liquid, interface and vapor phase respectively. The temperature readings were taken right at the middle of the chamber to obtain symmetricalness at the relative steady state. From the experiment finding on an open condition experiment of top heating, the variation of temperature can go up to 2.57°C. This variation caused a surface tension driven convection that enhance the evaporation rate. The buoyancy driven convection for top heating was absent due to lower density at the interface relative to density at deeper part of water. The heat conduction for both top and bottom heating were low as compared to heat convection suggesting that heat convection is a dominant mode of heat transfer. The efficiency of the top heating was slightly better than the bottom heater. This experiment finding was in contrast with the Stefan’s condition because heat convection is significant and cannot be neglected. Another part of the experiment is to investigate the evaporation rate under vacuum condition. A vacuum chamber was designed to have two degrees of freedom to allow accurate positioning of the thermocouples with the plastic chamber that holds the liquid. The temperatures were quickly taken when steady state was achieved. Although buoyancy convection was present for top heating, the effect of thermocapillary convection can still be seen through the higher evaporation rate of top heating compared to bottom heating. The variation of temperature along the interface, up to 4.61°C caused the evaporation rate 1.35 times higher than the bottom heating.